Penerapan Metode Agile Pada Perancangan Sistem Informasi Pengajuan Nomor Surat di Pemerintahan Desa - Ismail, Abdul Rahman (Prodi Sistem Informasi Universitas Dharma Andalas, 2025)
The rapid advancement of information technology impacts various aspects of life, including the government sector. This study aims to design and develop a web-based letter number submission information system for village administration using the Agile method. This system is expected to make administrative processes more efficient and faster. Additionally, the digital service simplifies the process for both village officials and the community by eliminating the need for time-consuming manual procedures. Using the Agile method, the system is designed as expected. Based on White Box and Black Box testing, the system functions as intended. With these results, the system can be implemented to enhance administrative service efficiency at the village level.